Auramine-o and Malachite Green Poisoning: Rare and Fatal - Md, Hisham; A, Vijayakumar; N, Rajesh; MN, Sivakumar (Indian Journal of Pharmacy Practice)
Traditionally it was believed that the cow dung has germicide property. In modern era, due to unavailability of actual cow dung people started using commercially available synthetic one. The synthetic cow dung powder called 'Sani Powder' in local parlance used to clean courtyards, house and temple premises. It is a dye which can be a lethal poison with no available antidote. Cow dung powder is available in two different colors: yellow powder (Auramine-O) and green powder (Malachite Green), commonly used in rural Tamil Nadu (South India) in the districts of Coimbatore, Tirupur and Erode. Even though the sale is legally banned, the powder is easily available in grocery shops. High toxicity profile of the dye is evident from limited toxicological data demonstrated from clinical and experimental studies. Auramine is life threatening as it is neurotoxic and also causes severe hepatic damage. Animal and observational research confirms that Malachite Green is multi-organ toxin with delayed toxicity. Very few cases have been reported with Auramine poisoning while there are no references so far about Malachite Green poisoning.
Keywords: Auramine poisoning; Dye; Hepatotoxicity; Malachite Green; Neurotoxicity